Experimental analysis and development of novel drying kinetics model for drying grapes in a double slope solar dryer - Natarajan, Sendhil Kumar; Suraparaju, Subbarama Kousik; Muthuvairavan, Guna; Elangovan, E.; Mahendran, Samykano (Elsevier, 2024)
This experimental study aimed to evaluate the efficacy of natural and forced convective drying techniques in reducing the moisture content of the grapes in comparison with the conventional open sun drying method. Moisture effective diffusivity and activation energy were graphically determined using the Arrhenius equation. In the initial three-day period, forced convection drying significantly reduced moisture from 2000 g to 353 g, with a minimum loss of 14 g. In the next three days, natural convection reduced moisture from 2787 g to 468 g, with a minimum loss of 11 g. These outcomes were then compared to the results of open-sun drying. The investigation showed that open drying and natural convection methods eliminated 25.05 % and 82.35 % of the moisture content, respectively. However, for three days, open-sun drying removed 30.5 % of grape moisture, while forced convection achieved an impressive 83.21 % reduction. The study's innovative mathematical model explained drying curve characteristics, supported by correlation coefficients and parity plots. The comparison shows that the experimental moisture ratios and those predicted by the new correlation exhibit R2 values ranging from 0.984 to 0.994.